Online youth political engagement and bureaucratization: The Australian Youth Forum. (August 2019) - Pillay, Prashanth
Through in-depth interviews with all 10 youth representatives who worked in the Australian Youth Forum (AYF), Australia's first online government youth forum, this article explains how online engagement was experienced and understood by those who managed its day-to-day operation. While the AYF was decommissioned in 2014, it was the first, and, till date, only online federal initiative that invited young people to run a government-funded youth public forum. Despite its relatively short existence, the AYF provokes questions about the influence of historically entrenched political values on online youth political participation and policy. Findings from this article have uncovered a series of challenges faced by youth in adjusting to government efforts to regulate consultation within the AYF. Building on Collin's (2015, Young Citizens and Political Participation in a Digital Society: Addressing the Democratic Disconnect . London: Palgrave Macmillan.) observation of a 'democratic disconnect' in Australian youth policy, an incompatibility between government expectations of youth political involvement and how young people value participation, this article suggests that the AYF provided key insights into the centralized bureaucratic arrangements that have historically defined Australian youth participation and how they influence youth participatory experiences in online government initiatives.